Doing Phenomenological Research in Hematology: The Experience and Benefits According to Researchers' Perspective - Mirta Rocchi; Luca Ghirotto; Cristina Pedroni (University of Bologna, 2023)
Doing phenomenological research entails a complex process that is only minimally published in scientific journals. What is often missing reflects how being in research calls into question the researchers themselves. Anyone who has conducted qualitative empirical research knows that personal engagement does not come at no cost; there are multiple pedagogical and professional practice gains. This article's aim is to share the phenomenology behind phenomenology: the reflection and personal experience of doing/being in phenomenological research and the personal narrative of what this experience has meant concerning the authors' own context: health care and nursing. Taking advantage of a conducted research exploring the lived experience of family caregivers of hematological patients assisted at home, we propose considerations about the perceived epistemic and cognitive gains, the formative and personal/professional sequels of having been reflective participants of phenomenologically oriented research.